Correlation Between Mex-Sledai and Mean Platelet Volume In Systemic Lupus Erythematosus Patients - Ayu Paramaiswari; Dody Hendro Susilo; Deddy Nur Wachid Achadiono (Indonesian Rheumatology Association, 2020)
A B S T R A C TBackground. Systemic lupus erythematosus (SLE) is a chronic autoimmunedisease which has a variety of clinical phenotypes with a complex clinical course.The clinical phenotypes are highly variable which can be characterized by acuteattacks, active periods, controllable or remission. Mean platelet volume (MPV) is astraightforward accessible indicator of platelet activity and is associated withsystemic inflammation. The routine usage of MPV as markers for disease activityin SLE remains problematic. Early detection of disease progression is pivotal in themanagement of SLE for obtaining better outcomes. Objective. The study aimed toconfirm that the measurement of the disease severity in patients with SLE usingMex-SLEDAI has a negative correlation with the decrease of MPV value. Methods.This cross-sectional analytic descriptive study was conducted using secondary datafrom the medical records of patients with SLE older than 18 years of age who werenot taking antiplatelets in the Internal Medicine policlinic of Dr. Sardjito GeneralHospital in 2018. Patients with a previous history of cardiovascular andcerebrovascular events, malignancies, receiving a treatment for infections,including sepsis, chronic infections (i.e. tuberculosis, cytomegalovirus, herpessimplex, herpes zoster), HIV, hepatitis B or hepatitis C, and incomplete data ofmedical record were excluded. The correlation between SLEDAI Mex and MPVvalues was evaluated using the Spearman's correlation test. Results. Sixty-sevensubjects (65 women, 2 men) aged 34 ± 11 years were recruited in the study. Themedian duration of diagnosis was 38,2 ± 45,7 months. Arthritis, skin rash andphotosensitivity were identified in 81,1%, 53,7%, and 46,3% of patients,respectively. The Mex-SLEDAI score ranged from 0 to 16. The average of MPV valueis 9.73 ± 1.21 fL. A significant correlation between MPV and SLEDAI Mex wasobserved (p = 0.03 (p <0.05), r = -0.255). Conclusion. The more severe SLE diseaseactivity (based on the Mex-SLEDAI scoring), the more negative correlation with theMPV value.